Kondisi Sosial Ekonomi Keluarga Sebagai Faktor Penentu Keberhasilan Pembagunan ( Suatu Studi di Kecamatan Malalayang ) - Renyaan, Lidya; Pangkey, Masje Silija; Rorong, Arie Junus (Sam Ratulangi University, 2015)
Abstract: Social condition is a state in a country at a given time. Economics is defined as the use ofmoney, power, precious time (Poerwodarminta, 1990). The purpose of the socio-economicconditions in this study were the circumstances or background of a family related to education,employment, income and socio-economic keluarga.Kondisi in this study were standing or positionof a person or family in the community with regard to the level of education, level income propertyor facility ownership and type of residence. The successful development of an achievement ofdevelopment that has been planned in order to create a more advanced state of society and modern.In this case the development is the pioneer of the government, both central and local pemeritah. Aregion is successful in doing development if the people in that area is no longer living under thepoverty line, capable of creating jobs for others, and on the mark with good economic turnaround.The method used in this research is descriptive and explanatory survey using a quantitativeapproach. As for the variables in this study are: socio-economic condition of the family and thesuccess of the development. By Arikunto (2002) argues that